Record of Cinnamomum verum (Lauraceae) as a host for treehoppers (Hemiptera, Auchenorrhyncha: Aetalionidae and Membracidae) - Glauco C. de S. Oliveira (Entomological Communications)
Cinnamon plants are attacked by different phytophagous insects, but there are no records of infestations by treehoppers. Thus, this note reports Notogonioides erythropus (Burmeister, 1835), Talipes appendiculatus (Fonseca, 1936), and Bolbonota sp. (Hemiptera: Membracidae) using a cinnamon tree as a host in an urban area of southeastern Brazil. Additionally, the formation of an interspecific aggregation between the leafhopper Aethalion reticulatum (Linnaeus, 1767) (Hemiptera: Aetalionidae) and N. erythropus is recorded.